PI Controller Design Using Model Reference Adaptive Control Approaches For A Chemical Process - M. R., Sapiee; Abdullah, F.; Noordin, A.; Jahari, A. N. (2008)
This paper discusses the application of Model Reference Adaptive Control (MRAC) concepts in designing an adaptive feedback controller to tune a given PI controller. The approaches of using the gradient (MIT) and stability (Lyapunov) methods are shown. The effectiveness of the two methods are shown through simulation and comparison is made to show which method give the best result. The results show that the stability method produces a better result.